Interactive PowerPoint Media on Thematic Learning in Primary School - Reinita; Mifthahul Jannah; Ferdian Admil Sandika (Universitas Pendidikan Ganesha, 2023)
Along with global technological advances, it affected all aspects of life, both in the economy, politics, culture, art and even in the world of education. Due to the lack of technology-based learning media, encouraging the development of useful PowerPoint interactive media in Grade IV Elementary Schools. The type of research used is development research (R&D) with the ADDIE development model. This development includes the analysis, design, development, implementation, and evaluation stages. Data collection uses a validation sheet filled out by material experts, linguists, and media experts and practicalities filled out by teachers and students. The test subjects in this study were students in grade IV Elementary School. The results showed the validity level was 92% for material, 90% for language and 95% for media, with a good category with an average of 92%. The level of practicality of the media shows an efficient category, with the results of the response questionnaire Obtaining a practicality percentage of 96%. While the results of the student response questionnaire with a practicality percentage of 93%. Based on the results of these data, interactive PowerPoint on thematic learning in schools can be used in the field because it has been declared valid and practical.